2012
DOI: 10.1177/0093854812437014
|View full text |Cite
|
Sign up to set email alerts
|

LIE Detection by Inducing Cognitive Load

Abstract: Research on the accuracy of eyewitness testimony has expanded dramatically in recent years. Most of it concerns the issue of mistaken identification, not the problem of uncovering deceptive accounts of witnesses, which is the focus of this research. In the literature, a technique for lie detection has been proposed that induces cognitive load on liars by averting their rehearsal of deception: Time Restricted Integrity-Confirmation. The current authors tested it by instructing "witnesses" of actual crime videos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
(117 reference statements)
0
20
0
4
Order By: Relevance
“…Other researchers defend the real-life application of even more artificial lie-detection methods, such as event-related potentials (Iacono, 2015). Other novel interviewing procedures, like TRI-Con (Walczyk et al, 2005, 2009, 2012) or reaction-time tests (Verschuere and De Houwer, 2011), are also similarly, “artificial.” Besides, presumably innocent suspects would not object to a procedure able to prove their innocence. However, before using new methods in real settings, replication studies are necessary, as well as ecologically valid research examining the limits of the procedures and potential countermeasures (Blandón-Gitlin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers defend the real-life application of even more artificial lie-detection methods, such as event-related potentials (Iacono, 2015). Other novel interviewing procedures, like TRI-Con (Walczyk et al, 2005, 2009, 2012) or reaction-time tests (Verschuere and De Houwer, 2011), are also similarly, “artificial.” Besides, presumably innocent suspects would not object to a procedure able to prove their innocence. However, before using new methods in real settings, replication studies are necessary, as well as ecologically valid research examining the limits of the procedures and potential countermeasures (Blandón-Gitlin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Walczyk et al (2005, 2009, 2012) introduced a more articulated interview approach called TRI-Con (Time Restricted Integrity-Confirmation) that involves posing questions to induce cognitive load during lying but facilitate responding during truth-telling. TRI -Con research has also yielded encouraging results (Walczyk et al, 2005, 2009, 2012). Based on this research, we also artificially increased the interviewees’ cognitive load to magnify the differences between liars and truth tellers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses showed that rehearsed deception is detectable. Finally, Walczyk et al (2012) tested TRI-Con in a forensically relevant context. “Witnesses” observed actual crime videos, then later told the truth or lied rehearsed or unrehearsed about them during interrogation.…”
Section: Lie Detection Via Inducing Cognitive Loadmentioning
confidence: 99%
“…Sujeitos mentindo produzem mais pistas para a classificação se solicitados, por exemplo, a contar os acontecimentos na ordem inversa (Vrij, Mann, Fisher, Leal, Milne, & Bull, 2008). Instruir suspeitos a manter contato visual durante a entrevista também produziu efeitos semelhantes (Doherty-Sneddon, Bruce, Bonner, Longbotham, & Doyle, 2002;Walczyk, Griffith, Yates, Visconte, Simoneaux, & Harris, 2012).…”
unclassified